Ubiquitination and Ubiquitin-Like Modifications as Mediators of Alternative Pre-mRNA Splicing in Arabidopsis thaliana - Lan, Wei; Qiu, Yuhao; Xu, Yun; Liu, Yalin; Miao, Ying (Frontiers in Plant Science, 2022)
The alternative splicing (AS) is a common process in eukaryotes, it has been implicated to play an irreplaceable role during plant development and in response to environmental cues through evoking differential alternative splicing (DAS) of downstream genes or splicing factor itself (e.g., Serine/arginine-rich (SR) proteins). Numerous studies have shown that loss of alternative splicing components can lead to plant growth and development defects and stress-sensitive phenotypes. An increasing report about the post-translational modification (PTM) of alternative splicing components reveals that PTM plays crucial roles in regulating the activity, stability, localization, interactions or folding of proteins including spliceosomal proteins in human cells and yeast cells, which may support another layer regulation of alternative splicing. Here we summarize the recent reports concerning ubiquitin and ubiquitin-like modification of spliceosome components and analyze the relationship between spliceosome and the ubiquitin (Ub)/26S proteasome pathway in plants. Comparison with animal cells, we speculate the roles of protein ubiquitination mediating alternative splicing in plant development and environment response.